What is the value of y(π
2
)
y(π2) where y
′′
−2y
′
+y=xe
x
sinx
y″−2y′+y=xexsinx ; y(0)=0
y(0)=0 and y
′
(0)=1
y′(0)=1 ?
"k^2-2k+1=0"
"k_{1,2}=1"
"Y=c_1e^x+c_2xe^x"
"y(x)=c_1(x)e^x+c_2(x)xe^x"
"y_1(x)\\frac{dc_1(x)}{dx}+y_2(x)\\frac{dc_2(x)}{dx}=0"
"\\frac{dy_1(x)}{dx}\\frac{dc_1(x)}{dx}+\\frac{dy_2(x)}{dx}\\frac{dc_2(x)}{dx}=xe^xsinx"
"e^x\\frac{dc_1(x)}{dx}+xe^x\\frac{dc_2(x)}{dx}=0"
"\\frac{d}{dx}e^x\\frac{dc_1(x)}{dx}+\\frac{d}{dx}(xe^x)\\frac{dc_2(x)}{dx}=xe^xsinx"
"\\frac{d}{dx}e^x\\frac{dc_1(x)}{dx}+\\frac{d}{dx}(xe^x+e^x)\\frac{dc_2(x)}{dx}=xe^xsinx"
"\\frac{d}{dx}c_1(x)=-x^2sinx"
"\\frac{d}{dx}c_2(x)=xsinx"
"c_1(x)=c_3+\\int(-x^2sinx)dx"
"c_2(x)=c_4+\\int xsinxdx"
"c_1(x)=c_3+x^2cosx-2xsinx-2cosx"
"c_2(x)=c_4-xcosx+sinx"
"y(x)=c_3e^x+c_4xe^x-xe^xsinx-2e^xcosx"
"y(0)=c_3-2=0\\implies c_3=2"
"y'(x)=c_3e^x+c_4xe^x+c_4e^x-e^x(sinx+xcosx)-xe^xsinx-2e^xcosx+2e^xsinx"
"y'(0)=c_3+c_4-2=1\\implies c_4=1"
"y(x)=2e^x+xe^x-xe^xsinx-2e^xcosx"
"y(\\pi\/2)=9.62"
Comments
Leave a comment